Cell-Free DNA Sequencing Reveals Gene Variants in DNA Damage Repair Genes Associated with Prognosis of Prostate Cancer Patients - Lieb, Verena; Abdulrahman, Amer; Weigelt, Katrin; Hauch, Siegfried; Gombert, Michael; Guzman, Juan; Bellut, Laura; Goebell, Peter; Stöhr, Robert; Hartmann, Arndt; Wullich, Bernd; Taubert, Helge; et al. (Cells, 2022)
In the present study, we further analyzed the data obtained in our previous study, where we investigated the cell-free DNA (cfDNA) of 34 progressive prostate cancer patients via targeted sequencing. Here, we studied the occurrence and prognostic impact of sequence variants according to their clinical pathological significance (CPS) or their functional impact (FI) in 23 DNA damage repair (DDR) genes with a focus on the ATM serine/threonine kinase gene (ATM). All patients had at least one DDR gene with a CPS or FI variant. Kaplan-Meier analysis indicated that the group with a higher number of CPS variants in DDR genes had a shorter time to treatment change (TTC) compared to the group with a lower number of CPS variants (p = 0.038). Analysis of each DDR gene revealed that CPS variants in the ATM gene and FI variants in the nibrin (NBN) gene showed a shorter TTC (p = 0.034 and p = 0.042). In addition, patients with CPS variants in the ATM gene had shorter overall survival (OS; p = 0.022) and disease-specific survival (DSS; p = 0.010) than patients without these variants. Interestingly, patients with CPS variants in seven DDR genes possessed a better OS (p = 0.008) and DSS (p = 0.009), and patients with FI variants in four DDR genes showed a better OS (p = 0.007) and DSS (p = 0.008). Together, these findings demonstrated that the analysis of cfDNA for gene variants in DDR genes provides prognostic information that may be helpful for future temporal and targeted treatment decisions for advanced PCa patients.
CRIS-Team Scopus Importer:2022-12-02
Keywords: ATM; cfDNA; DDR genes; NBN; prognosis; prostate cancer; sequence variants

Cell-free dna variant sequencing using plasma and ar-v7 testing of circulating tumor cells in prostate cancer patients - Lieb, Verena; Bellut, Laura; Abdulrahman, Amer; Weigelt, Katrin; Hauch, Siegfried; Gombert, Michael; Guzman, Juan; Goebell, Peter; Stöhr, Robert; Hartmann, Arndt; Wullich, Bernd; Taubert, Helge; et al. (Cells, 2021)
Prostate cancer (PCa) is the second most common malignant cancer and is a major cause of morbidity and mortality among men worldwide. There is still an urgent need for biomarkers applicable for diagnosis, prognosis, therapy prediction, or therapy monitoring in PCa. Liquid biopsies, including cell-free DNA (cfDNA) and circulating tumor cells (CTCs), are a valuable source for studying such biomarkers and are minimally invasive. In our study, we investigated the cfDNA of 34 progressive PCa patients, via targeted sequencing, for sequence variants and for the occurrence of CTCs, with a focus on androgen receptor splice variant 7 (AR-V7)-positive CTCs. The cfDNA content was associated with overall survival (OS; p = 0.014), disease-specific survival (DSS; p = 0.004), and time to treatment change (TTC; p = 0.001). Moreover, when considering all sequence variants grouped by their functional impact and allele frequency, a significant association with TTC (p = 0.017) was observed. When investigating only pathogenic or likely pathogenic gene variants, variants of the BRCA1 gene (p = 0.029) and the AR ligand-binding domain (p = 0.050) were associated with a shorter TTC. Likewise, the presence of CTCs was associated with a shorter TTC (p = 0.031). The presence of AR-V7-positive CTCs was associated with TTC (p < 0.001) in Kaplan–Meier analysis. Interestingly, all patients with AR-V7-positive CTCs also carried TP53 point mutations. Altogether, analysis of cfDNA and CTCs can provide complementary information that may support temporal and targeted treatment decisions and may elucidate the optimal choice within the variety of therapy options for advanced PCa patients.
CRIS-Team Scopus Importer:2021-11-26
Keywords: CfDNA; CTCs; Prognosis; prostate cancer; Sequence variants

Expression of AR-V7 (Androgen receptor variant 7) protein in granular cytoplasmic structures is an independent prognostic factor in prostate cancer patients - König, Paul; Eckstein, Markus; Jung, Rudolf; Abdulrahman, Amer; Guzman, Juan; Weigelt, Katrin; Serrero, Ginette; Hayashi, Jun; Geppert, Carol-Immanuel; Stöhr, Robert; Hartmann, Arndt; Wullich, Bernd; et al. (Cancers, 2020)
Prostate cancer (PCa) is the second most common cancer, causing morbidity and mortality among men world-wide. The expression of the androgen receptor (AR) and its splice variants is a crucial factor of prostate cancer biology that has not been comprehensively studied in PCa tumors. The aim of this study was to characterize the protein expression of the AR and its splice variant, AR-V7, and their subcellular distributions in PCa by immunohistochemistry and to correlate the results to the clinicopathological data and prognosis. Immunohistochemical staining for AR and AR-V7 was performed on a tissue microarray (TMA) with specimens from 410 PCa patients using an immunoreactive score (IRS) or only the percentage of AR-V7 staining in cytoplasmic granules. Nuclear or cytoplasmic AR staining was not associated with prognosis. AR-V7 staining was only occasionally observed in the nucleus. However, AR-V7 staining in the cytoplasm or in cytoplasmic granules was associated with relapse-free survival (RFS). AR-V7 staining of the cytoplasm was associated with a shorter RFS, whereas AR-V7 staining of cytoplasmic granules was associated with a longer RFS. In a multivariate Cox’s regression analysis, only negative (<5%) AR-V7 staining of cytoplasmic granules remained an independent prognostic factor for RFS (HR = 5.3; p = 0.006). In a further subgroup analysis by multivariate Cox’s regression analysis, AR-V7 was an independent prognostic factor in the following groups: age ≤ 65 (HR = 9.7; p = 0.029), negative CK20 staining (HR = 7.0; p = 0.008), and positive perineural invasion (HR = 3.7; p = 0.034). Altogether, AR-V7 protein in granular cytoplasmic structures is an independent prognostic factor for RFS in PCa patients.
CRIS-Team Scopus Importer:2020-09-25
Keywords: AR; AR-V7; Gleason score; Perineural invasion; Prognosis; Prostate cancer; Relapse-free survival; RFS

Progranulin (GP88) is an independent prognostic factor for prostate cancer patients - Taubert, Helge; Abdulrahman, Amer; Eckstein, Markus; Jung, Rudolf; Guzman, Juan; Weigelt, Katrin; Serrero, Ginette; Yue, Binbin; Geppert, Carol-Immanuel; Stöhr, Robert; Hartmann, Arndt; Wullich, Bernd; et al. (CANCER RESEARCH, 2020)
CRIS-Team WoS Importer:2021-03-05